KARAKTERISTIK KASUS BENDA ASING PADA TELINGA DI INSTALASI GAWAT DARURAT RSUP DR. M. DJAMIL PADANG PERIODE 2017 – 2021 - Javandi, Muhammad Rayhan Abiyyu; Huriyati, Effy; Saputra, Deddy; Rahman, Sukri; Firdawati, Firdawati; Revilla, Gusti (SINERGI : Jurnal Riset Ilmiah, 2025)
Foreign body in the ear is an emergency case in the field of ENT-KL which is often found in the emergency room. Foreign objects found can be insects, seeds, cotton buds, batteries, and others. Foreign objects in the form of insects can cause irritation so that the patient will feel pain. Therefore, for live foreign objects, first aid efforts are needed in the form of dropping edible oil into the ear so that the live foreign objects die and then immediately take them to the nearest health facility. The purpose of this study was to determine the characteristics of cases of foreign bodies in the ear at the emergency department of Dr. M. Djamil Padang for the period 2017 – 2021. This type of research is a retrospective descriptive with a total sampling technique and uses secondary data. Samples that met the inclusion and exclusion criteria were 707 cases. The results of this study showed that the most characteristic distribution of foreign body cases in the ear was: the age group of children (43.4%), male sex (59.3%), types of inorganic foreign bodies (66.2%) with objects foreigncotton bud (49.2%), no symptoms (78.3%), no first aid efforts (86.2%), treatment with extraction (70.2%), and no complications (86%). The conclusion of this study is that the most foreign bodies found in the ear are cotton buds, so education is needed to the public about the use of cotton buds.